Economic incentives of application of environmental measures by agricultural land users - Dorosh О.; Fomenko, V.; Zastulka, Illia-Ol.; Tretiachenko, D. (Land Management, Cadastre and Land Monitoring, 2021)
During the analysis of legislation, regulations and their practical implementation we identified problems of maintaining the required level of environmental safety of agricultural land use. In this regard, the incentive of environmental measures implemented by economic entities in the agricultural sector is essential both by the state and through the intensification of private initiative. It is substantiated that due to the competent combination of parameters and tools of the regulator, landowners and land users will honestly comply with the requirements of environmental safety in land use. It is proposed to introduce changes to the legislation with a clear definition of the sources, grounds, procedure for compensation payments for implementation of environmental protection measures by agricultural land use entities. It is expedient to intensify the system of joint funds for restoration, reproduction and protection of agricultural lands. Key words: economic incentive for rational use and protection of lands, nature protection measures, agrarian land use, landowners and land users.